CT imaging prior to transcatheter aortic valve implantation in the UK. Issue 1 (6th April 2020) - Harries, Iwan; Weir-McCall, Jonathan R; Williams, Michelle C; Shambrook, James; Roditi, Giles; Bull, Russel; Morgan-Hughes, Gareth J; Nicol, Edward D; Moss, Alastair J
Abstract : Objective: This cross-sectional observational study sought to describe variations in CT in the context of transcatheter aortic valve implantation (CT-TAVI) as currently performed in the UK. Methods: 408 members of the British Society of Cardiovascular Imaging were invited to complete a 27-item online CT-TAVI survey. Results: 47 responses (12% response rate) were received from 40 cardiac centres, 23 (58%) of which performed TAVI on-site (TAVI centres). Only six respondents (13%) performed high-volume activity (>200 scans per year) compared with 13 (28%) performing moderate (100–200 scans per year) and 27 (59%) performing low (0–99 scans per year) volume activity. Acquisition protocols varied (41% retrospective, 12% prospective with wide padding, 47% prospective with narrow padding), as did the phase of reporting (45% systolic, 37% diastolic, 11% both, 6% unreported). Median dose length product was 675 mGy.cm (IQR 477–954 mGy.cm). Compared with non-TAVI centres, TAVI centres were more likely to report minimum iliofemoral luminal diameter (n=25, 96% vs n=7, 58%, p=0.003) and optimal tube angulation for intervention (n=12, 46% vs n=1, 8%, p=0.02). Conclusions: This national survey formally describes current CT-TAVI practice in the UK. High-volume activity was only present at one in seven cardiac CT centres. There is wide variation in scan acquisition, scan reporting and radiation dose exposure in cardiac CT centres.